MOURNING AND WEEP IN THE CREATION OF ALISHER NAVOY (Scientific journal of the Fergana State University, 2023)
The article analyzes the lamentations of Alisher Navoi dedicated to the death of his teacher Abdurahmon Jami. At the same time, the analysis of the commentaries shows that the poet's philosophical views and teachings are embedded in the verses. The analysis emphasizes the friendship, human relationship and qualities between the two individuals. Comments are made on the poet's skill in the use of words in the artistic expression of the peculiarities of the mourning ceremony in Marsiye.